Dynamics of sediment disturbance by periodic artificial discharges from the world's largest tidal power plant. (5th May 2017) - Kim, J.W.; Ha, H.K.; Woo, S.B.
Abstract: To investigate the dynamics of sediment disturbance near the world's largest Sihwa tidal power plant (TPP), two mooring observations have been conducted. The mooring results show that current velocity and suspended sediment concentration (SSC) were significantly disturbed over various time scales. On the short-term (flood−ebb) time scale, resuspension of bottom sediment is mainly controlled by the strong jet-flow (>2 m s −1 ) and resulting anticlockwise rotating vortex associated with the artificial discharge. During ebb phase, the strong flow resulted in suspension of high-concentration near-bed sediment and seaward transport of the suspended sediment. After turning to flood phase, the vortex produced secondary SSC peaks, transporting the suspended sediment toward the Sihwa TPP. The most active suspension of bed sediment predominantly occurred during 1–2 h immediately after the start of artificial discharge. For the fortnightly (spring−neap) time scale, SSC during spring tide was approximately 2–5 times higher than that during neap tide. During the combined period of ebb and spring tides, in particular, the periodic artificial discharge can enhance the responses of SSC in the vicinity of Sihwa TPP. Highlights: Sediment disturbance near the world's largest tidal power plant was investigated using mooring observations. Strong jet-flow and resulting anticlockwise rotating vortex are key controlling factors in eroding the bed sediment. The most active suspension of bed sediment occurred during 1–2 h immediately after the start of discharge.